Revolusi Industri 4.0 - Astika Sukma Diyani; Dani Fajar Assidqi; Melisa Handayani; Naerul Edwin Kiky Aprianto; Rafli Zakaria (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Industry is one of the main points in a kind of regional economy which has the strength to support the economy in a developed region and is strong in competition. In technological developments that continue to grow rapidly, industry must be able to improve a method or strategy when experiencing globalization. Industry 4.0 ushers in an era of digital transformation that integrates advanced technologies such as the Internet of Things (IoT), artificial intelligence (AI), and automation into industrial processes. The aim of this research is to analyze the readiness of the Indonesian industrial market to face the challenges and opportunities of the Industrial Revolution 4.0. This study uses various readiness indicators such as technological infrastructure, human resources and government policies to assess the extent to which Indonesian industry utilizes digital technology to increase productivity, efficiency and global competitiveness. Despite significant progress, some sectors still face challenges in technology adoption, skills development and infrastructure support. Recommendations are provided to accelerate industrial readiness to face global change through collaboration between government, the private sector and educational institutions. This research aims to analyze Indonesia's readiness to face the industrial revolution 4.0.